Terlipressin in obstetric and gynecological practice: a case of a missed miscarriage in late pregnancy complicated by bleeding. Case report - Vitaly B. Tskhay; Pavel K. Yametov; Yuriy S. Raspopin; Natalia M. Yametova; Galina N. Polstyanaya; Daniil A. Ryabinin (Гинекология, 2023)
A few randomized multicenter studies indicate that prophylactic vasopressin in obstetric and gynecological surgeries is mainly safe and associated with a significant reduction in intraoperative blood loss. This article reviews recent scientific papers describing the use of vasopressin in obstetric and gynecological practice with an assessment of its effectiveness depending on the dose and route of administration. We present a clinical case demonstrating that drugs with a vasopressor effect, in particular terlipressin, in a patient with uterine bleeding after a late induced miscarriage allowed to obtain an excellent hemostatic effect and avoid the need for additional methods of surgical hemostasis.